2014
DOI: 10.1111/1462-2920.12438
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Bacillus subtilis carbon core metabolism to simultaneous nutrient limitation and osmotic challenge: a multi‐omics perspective

Abstract: The Gram-positive bacterium Bacillus subtilis encounters nutrient limitations and osmotic stress in its natural soil ecosystem. To ensure survival and sustain growth, highly integrated adaptive responses are required. Here, we investigated the system-wide response of B. subtilis to different, simultaneously imposed stresses. To address the anticipated complexity of the cellular response networks, we combined chemostat experiments under conditions of carbon limitation, salt stress and osmoprotection with multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 96 publications
4
76
0
4
Order By: Relevance
“…1) could be used by B. subtilis as nutrients, either as sole carbon or as sole nitrogen sources. We also tested the potential use of these compounds as nutrients under high salinity (0.6 M NaCl) growth conditions as we considered the possibility that their uptake would be stimulated by increased osmolarity of the growth medium von Blohn et al, 1997;Zaprasis et al, 2014). Catabolic routes for trans-4-hydroxy-L-proline, L-proline betaine and betonicine have been identified in a variety of micro-organisms (Kumar et al, 2014;Watanabe et al, 2012;White et al, 2012;Zhao et al, 2013), but we found that B. subtilis cannot use any of the studied L-proline derivatives as nutrients (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) could be used by B. subtilis as nutrients, either as sole carbon or as sole nitrogen sources. We also tested the potential use of these compounds as nutrients under high salinity (0.6 M NaCl) growth conditions as we considered the possibility that their uptake would be stimulated by increased osmolarity of the growth medium von Blohn et al, 1997;Zaprasis et al, 2014). Catabolic routes for trans-4-hydroxy-L-proline, L-proline betaine and betonicine have been identified in a variety of micro-organisms (Kumar et al, 2014;Watanabe et al, 2012;White et al, 2012;Zhao et al, 2013), but we found that B. subtilis cannot use any of the studied L-proline derivatives as nutrients (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Attesting to the critical role of compatible solute synthesis by micro-organisms for managing osmotic stress (Csonka, 1989;Kempf & Bremer, 1998), the genetic disruption of the osmotically inducible L-proline biosynthesis route causes an osmotically sensitive growth phenotype (Brill et al, 2011a). Osmostress protection of B. subtilis can also be achieved through L-proline uptake and the osmotically inducible OpuE transporter is key to this process von Blohn et al, 1997;Zaprasis et al, 2014). However, compared with the metabolically inert compatible solute glycine betaine (Boch et al, 1994), an exogenous supply of L-proline is not a particularly effective osmoprotectant for B. subtilis (Zaprasis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We are thus led to the conclusion that the higher growth yield of osmotically stressed cells cultured in the presence of Glu, Gln, Asp, Asn, Arg, Orn, and Cit than of those that did not receive an osmoprotective amino acid (Fig. 2) rests on the saving of precious biosynthetic building blocks and energy sources that would otherwise have to be devoted under high-osmolarity growth conditions (61) to the synthesis of the proline precursor glutamate (31,32) or of proline itself (31,51). The highly interconnected proline and arginine synthesis and degradation pathways of B. subtilis (34,48,49) (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The cellular adjustment of B. subtilis to high-osmolarity environments is a well-staged and complex process (61,(69)(70)(71). However, the effective management of water fluxes in or out of the cell (12,72) and the fine-tuning of the solvent properties of the cytoplasm (19,73) are key events that allow cell proliferation under otherwise growth-inhibiting conditions (7,11,13).…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis from various levels of "omics" data (transcriptomics, proteomic and metabolomics) is essential for understanding the entire behavior of cells during complex biological interactions [114]. Currently, this multi-omics approach has been used widely to study stress response in various organisms such as fungi, plants and bacteria [115][116][117]. However, to the best of our knowledge, there is no study that has been done that utilized multi-omic approaches to unravel dinoflagellates' complexity.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%